2020
DOI: 10.3390/bioengineering7030072
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols in Dental Applications

Abstract: (1) Background: polyphenols are a broad class of molecules extracted from plants and have a large repertoire of biological activities. Biomimetic inspiration from the effects of tea or red wine on the surface of cups or glass lead to the emergence of versatile surface chemistry with polyphenols. Owing to their hydrogen bonding abilities, coordination chemistry with metallic cations and redox properties, polyphenols are able to interact, covalently or not, with a large repertoire of chemical moieties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 155 publications
0
37
0
Order By: Relevance
“…The incorporation of PY into universal adhesives may influence their bonding performance to dentin and ameliorate the antibacterial effects against cariogenic species, such as S. mutans . An ideal restorative material should possess some antibacterial properties, along with good mechanical properties and bonding stability over time [ 1 , 21 , 36 ]. Unfortunately, the resin adhesive systems that are currently available on the market do not completely fulfill all these requirements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The incorporation of PY into universal adhesives may influence their bonding performance to dentin and ameliorate the antibacterial effects against cariogenic species, such as S. mutans . An ideal restorative material should possess some antibacterial properties, along with good mechanical properties and bonding stability over time [ 1 , 21 , 36 ]. Unfortunately, the resin adhesive systems that are currently available on the market do not completely fulfill all these requirements.…”
Section: Discussionmentioning
confidence: 99%
“…However, the bond strength and stability of resin adhesives bonded to dental tissues are important aspects to attain optimal dental restorations in an oral cavity [ 1 , 3 , 5 , 21 ]. Indeed, several studies [ 41 , 42 , 43 , 44 , 45 ] reported a severe degradation of the polymer–dentin interface over time due to a synergic hydrolytic degradation of the polymer matrix within the hybrid layer and to the enzymatic degradation of poorly infiltrated demineralized dentin collagen fibrils through activated host metalloproteinases (MMPs) and cysteine-cathepsins (CTs).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the good adhesive properties of ENR-50 and oral cavity-safe ingredients [ 32 , 33 , 34 ], such composites have the potential to be dedicated to self-healing long-term soft denture lining materials production [ 35 ]. However, more advanced, especially from the medical point of view, studies must be carried out in the future to confirm our presumptions.…”
Section: Introductionmentioning
confidence: 99%